Socioeconomics of Agriculture - Mann, Stefan (Cham Springer Nature, 2018)
Hierarchy; Cooperation; Agricultural systems; Governance; Primary sector; Socioeconomics; Agri-food chain; Agricultural economics
English
Keywords: Technology, engineering, agriculture; Hierarchy; Cooperation; Agricultural systems; Governance; Primary sector; Socioeconomics; Agri-food chain; Agricultural economics